A prion-like domain in Hsp42 drives chaperone-facilitated aggregation of misfolded proteins - Grousl, Tomas; Ungelenk, Sophia Maria; Ho, Chi-Ting; Khokhrina, Maria; Mayer, Matthias P.; Bukau, Bernd; Mogk, Axel (The journal of cell biology, 2018)
Chaperones with aggregase activity promote and organize the aggregation of misfolded proteins and their deposition at specific intracellular sites. This activity represents a novel cytoprotective strategy of protein quality control systems; however, little is known about its mechanism. In yeast, the small heat shock protein Hsp42 orchestrates the stress-induced sequestration of misfolded proteins into cytosolic aggregates (CytoQ). In this study, we show that Hsp42 harbors a prion-like domain (PrLD) and a canonical intrinsically disordered domain (IDD) that act coordinately to promote and control protein aggregation. Hsp42 PrLD is essential for CytoQ formation and is bifunctional, mediating self-association as well as binding to misfolded proteins. Hsp42 IDD confines chaperone and aggregase activity and affects CytoQ numbers and stability in vivo. Hsp42 PrLD and IDD are both crucial for cellular fitness during heat stress, demonstrating the need for sequestering misfolded proteins in a regulated manner.
Gesehen am 20.05.2019